Seeking harmony amidst diversity: Consensus building with network externalities - Chia-Hui Chen; Junichiro Ishida (Osaka University, Institute of Social and Economic Research (ISER), 2011)
A group of individuals, with a potential conflict of interest, face a choice among alternatives. There is a network externality such that the chosen alternative yields value only if sufficiently many individuals get on board. Their preferences for each alternative and the benefit derived from a successfully formed network are known only privately and might vary between the players who determine whether to make their choices early or late. We characterize the equilibrium timing of adoption as well as the efficient timing which maximizes the total expected payoff. We also show that the efficient timing of adoption can be implemented by a simple fee scheme. The analysis gives an insight into why consensus is often hard-won in some societies and suggests a potential role of social norms in improving the efficiency.
Keywords: 330; Soziale Norm; Soziales Verhalten; Netzwerkökonomik; Präferenztheorie; Kollektives Handeln